ANALISIS KESESUAIAN PENEMPATAN DAN GAYA KEPEMIMPINAN TRANSAKSIONAL TERHADAP KINERJA PEGAWAI MELALUI KOMITMEN ORGANISASI PADA PT. BANK SULSELBAR MAKASSAR - Ade Pratiwi Putri; Abdul Samad; Novita Rosanti; Muhammad Nasir (Program Pasca Sarjana IBK Nitro, 2023)
The purpose of this study was to determine and analyze the effect of suitability for job placement and transactional leadership style on organizational commitment and employee performance, to determine and analyze the effect of organizational commitment on employee performance, to determine and analyze the effect of suitability for job placement and transactional leadership style on employee performance through organizational commitment to PT. Bank Sulselbar Makassar. The data analysis technique used is descriptive analysis and path analysis. The results showed that work placement had a positive and significant effect on organizational commitment, leadership style had a positive and significant effect on organizational commitment. Work placement has a positive and significant effect on employee performance, leadership style has a positive and significant effect on employee performance, organizational commitment has a positive and significant effect on employee performance. Organizational commitment can mediate the effect of work placement and leadership style on employee performance at PT. Bank Sulselbar Makassar